Dung beetles (Scarabaeidae: Scarabeinae) from the Reserva Nacional Tambopata, Madre de Dios, Peru - Figueroa, Luis (2011)
This study reports the species of Scarabaeinae (Coleoptera: Scarabaeidae) collected in Tambopata National Reserve in 2009. A total of 38 species and 874 individuals were collected. The tribe Canthonini showed the highest diversity and abundance. Coprophagy is clearly preferred over necrophagy by the dung beetle fauna in the area. A comparison of the species collected during the rainy and dry seasons is presented.